Carbon The Black, the Gray and the Transparent - Gupta, Tapan (Springer International Publishing : Imprint: Springer, 2018)
All living things contain carbon in some form, as it is the primary component of macromolecules including proteins, lipids, nucleic acids (RNA and DNA), and carbohydrates. As a matter of fact, it is the backbone of all organic (chemistry) compounds forming different kinds of bonds. Carbon: The Black, the Gray and the Transparent is not a complete scientific history of the material, but a book that describes key discoveries about this old faithful element while encouraging broader perspectives and approaches to its research due to its vast applications. All allotropes of carbon are described in this book, along with their properties, uses, and methods of procurement or manufacturing. Black carbon is represented by coal, gray carbon is represented by graphite, and transparent carbon is represented by diamond.